U.S. private investment and economic aid in underdeveloped countries. - Marcus, Wil. (Washigton, Public Affairs Institute, 1959)
The report contains an highlights on private investment and government aid in underdeveloped nations
Includes bibliography.
obn 24/10/2019
Loans
Keywords: Investments, American; Economic assistance, American; Developing countries